Pengaruh Pemberian Berbagai Jenis Pupuk Kandang Terhadap Pertumbuhan Bibit Tanaman Kopi Robusta (Coffea canephora L) Pada Tanah Ultisol Di Polybag - Hayata Hayata; Ridawati Marpaung; Annisa Berliana Putri (Universitas Batanghari, 2023)
This research aims to determine the effect of applying cow manure, goat manure and chicken manure on the seedlings growth of robusta coffee (Coffea cenophora L) in ultisol soil in polybags. This research was carried out since January to April 2023 at Pijoan Gardens, Campus II, Batanghari University and Laboratory of Batanghari University. The design used in this research was a completely randomized design (CRD) with one treatment factor, i.e. various types of manure which consist of 4 (four) treatment levels, namely: k0 : 3000 g of soil media without treatment (control), k1: 30 g cow manure + 3000 g ultisol soil, k2: 30 g goat manure + 3000 g ultisol soil, k3: 30 g chicken manure + 3000 g ultisol soil. Each treatment was repeated 3 (three) times. The parameters observed were soil water content, plant height, stem diameter, crown dry weight, root dry weight and root shoot ratio. The treatment of various types of manure had a significant effect on plant height, stem diameter, crown dry weight and root dry weight, but it had no significant effect on the root-shoot ratio of Robusta coffee seedlings. When this is compared with the control one, so the application of goat manure in treatment k2: 30 g of goat manure + 3000 g of ultisol soil gave the highest average results in several parameters such as plant height (79.00 cm) increasing 29.16%, stem diameter (8.40 mm) increased 38.84%, crown dry weight (24.84 g) increased 149.39% and root dry weight (11.09 g) increased 114.92%, and root shoot ratio (2.32) increased 20.83%, There were changes in the chemical characteristics of the soil, including the initial pH of 5.65 to 6.43-6.48 beside the highest soil water content was found in the k2 treatment at 11.99%.Key words: manure (cow, goat, chicken), growth, Liberica coffee, ultisol.